2020
DOI: 10.1152/ajprenal.00051.2020
|View full text |Cite
|
Sign up to set email alerts
|

Urine cytokines as biomarkers for diagnosing interstitial cystitis/bladder pain syndrome and mapping its clinical characteristics

Abstract: The objective of the present study was to investigate the diagnostic values of urine cytokines in patients with interstitial cystitis/bladder pain syndrome (IC/BPS) and to identify their correlations with clinical characteristics. Urine samples were collected from 127 patients with IC/BPS [European Society for the Study of Interstitial Cystitis (ESSIC) types 1 and 2] and 28 controls. Commercially available multiplex immunoassays (MILLIPLEX map kits) were used to analyze 31 targeted cytokines. Cytokine levels b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 32 publications
1
53
0
1
Order By: Relevance
“…Niimi et al reported that urine CXCL10 was not increased in 25 non-Hunner type IC/BPS patients in compared with 31 controls 17 . However, in our previous study with 127 non-Hunner type IC/ BPS patients and 28 controls, urine CXCL10 levels were not only significantly increased in IC/BPS patients but also correlated with the glomerulation grade and maximal bladder capacity 11 . Eotaxin-1, acting as a selective chemoattractant for eosinophils, is implicated in many eosinophilic inflammatory diseases 18 .…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Niimi et al reported that urine CXCL10 was not increased in 25 non-Hunner type IC/BPS patients in compared with 31 controls 17 . However, in our previous study with 127 non-Hunner type IC/ BPS patients and 28 controls, urine CXCL10 levels were not only significantly increased in IC/BPS patients but also correlated with the glomerulation grade and maximal bladder capacity 11 . Eotaxin-1, acting as a selective chemoattractant for eosinophils, is implicated in many eosinophilic inflammatory diseases 18 .…”
Section: Discussionmentioning
confidence: 68%
“…MCP-1, CXCL10, and RANTES are known to be upregulated and involved in chemokine signaling in peripheral neuroinflammatory responses 16 . These cytokines were elevated in IC/BPS urine specimens, suggesting neuropathic inflammation, as well as afferent hypersensitivity within the bladder 11 . Niimi et al reported that urine CXCL10 was not increased in 25 non-Hunner type IC/BPS patients in compared with 31 controls 17 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations